Pengaruh Herbisida Nabati Untuk Menekan Pertumbuhan Gulma Tridax procumbens Pada Kebun Jeruk - Setyo Andi Nugroho; Salim, Abdurrahman; Jumiatun (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2023)
Indonesia's orange production in 2014 increased from 1.78 million tonnes to 2.16 million tonnes. In 2016 orange production decreased by 2,212 tons. The decline in orange production was caused by weeds. Weeds cause a reduction in crop yields of up to 61%. The research aims to identify the types of weeds and the secondary metabolic potential of dominant weeds in citrus plants. The research results showed 10 families, 23 species and 400 individual weeds. The weed that has the highest SDR value is the grass type Tridax procumbens with a Summed Dominance Ratio (SDR) value of 7.28%. Phytotoxicity in Tridax procumbens leaf plants is P4 with a concentration of 80g/l of 45.33. Wet weight and dry weight affect the P4 concentration with a concentration of 80g/l that most inhibits the growth of Tridax procumbens. Kirinyuh plants contain flavonoids of 250.24 mg/L, phenolics of 265.75 mg/L, and tannins of 242.38 mg/L. The high levels of phenolic compounds in kirinyuh weed have the potential to be used as a bioherbicide.